1994
DOI: 10.1099/0022-1317-75-8-1849
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of virus particles, infectious subviral particles, cores and VP7 crystals of African horsesickness virus serotype 9

Abstract: Methods were developed for the purification, at high yield, of four different particle types of African horsesickness virus serotype 9 (AHSV-9). These products included virus particles purified on CsC1 gradients which contain proteins apparently directly comparable to those ofbluetongue virus (VP1 to VP7); virus particles purified on sucrose gradients which also contain, as a variable component, protein NS2; infectious subviral particles (ISVPs), containing chymotrypsin cleavage products of VP2; and cores, obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 21 publications
2
47
0
Order By: Relevance
“…1C). Autonomous crys-tal formation in vivo is a feature unique to AHSV VP7 amongst the orbiviruses (Burroughs et al, 1994;Maree and Paweska, 2005). No similar structures to those described above were observed in wild-type baculovirus-infected cells (Fig.…”
Section: Synthesis and Characterization Of Ahsv Clps Composed Of Vp3 mentioning
confidence: 75%
See 3 more Smart Citations
“…1C). Autonomous crys-tal formation in vivo is a feature unique to AHSV VP7 amongst the orbiviruses (Burroughs et al, 1994;Maree and Paweska, 2005). No similar structures to those described above were observed in wild-type baculovirus-infected cells (Fig.…”
Section: Synthesis and Characterization Of Ahsv Clps Composed Of Vp3 mentioning
confidence: 75%
“…1E), which is typical for authentic AHSV core particles (Fig. 1F), as described by Oellermann et al (1970) and Burroughs et al (1994). The icosahedral particles also displayed knob-like protrusions that radiated outwards, which is characteristic of the orbivirus ring-like arrange-ment of VP7 capsomers (Fig.…”
Section: Synthesis and Characterization Of Ahsv Clps Composed Of Vp3 mentioning
confidence: 83%
See 2 more Smart Citations
“…When AHSV VP7 is expressed in mammalian or insect cells, the protein trimers localise to one or two sites in the cell and assemble into large flat hexagonal crystalline particles (Burroughs et al 1994;Venter et al 2014) which have recently been shown to impede the formation of core-like particles (Maree et al 2016). This characteristic is unique to AHSV, and presents a distinct difference between major capsid protein VP7 of AHSV and BTV (Monastyrskaya et al 1997).…”
Section: Discussionmentioning
confidence: 99%